Frontal lobe degeneration of non-Alzheimer type and Pick's atrophy: Lumping or splitting? - Schmitt, Horst Peter; Yang, Yan; Förstl, Hans (European archives of psychiatry and clinical neuroscience, 1995)
We report six cases of presenile (five) and senile (one) progressive dementia with a mild-to-marked frontal or frontotemporal atrophy and ventricular dilation (Frontal Lobe Degeneration [FLD]). The most prominent microscopic features were layer-dependet neuronal depletion of the cortex, spongiosis, and cortical and subcortical gliosis. Five cases showed additional degeneration of the S. nigra, and two also had motor neuron disease. Despite the absence of Pick cells and bodies, such cases have many features in common with Pick atrophy. Because Pick cells and bodies are inconstantly occurring features in other-wise typical cases of Pick atrophy, they cannot be regarded as inevitable markers of the latter. In our opinion, cases with mild frontal or frontotemporal atrophy as described herein and by others match the grades 1 and 2 in terms of Schneider's classification of Pick atrophy [37]. As long as the etiology of both Pick atrophy and the socalled FLD is unknown, and we finally have to follow morphological criteria for classification, there is apparently no convincing reason to introduce a separate category, such as FLD or FTA, for the cases with moderate or mild frontal atrophy and dementia of frontal lobe type, which can be sufficiently classified with the Pick spectrum of lobar atrophy.